Intestinal Perforation in ACTH-Dependent Cushing's Syndrome. (13th March 2019) - Shahidi, Mariam; Phillips, Richard A.; Chik, Constance L.
Abstract : Previous studies have linked systemic glucocorticoid use with intestinal perforation. However, the association between intestinal perforation and endogenous hypercortisolism has not been well described, with only 14 previously published case reports. In this study, we investigated if intestinal perforation occurred more frequently in patients with ectopic ACTH syndrome and in those with a greater than 10-fold elevation of 24-hour urinary free cortisol level. Of 110 patients with ACTH-dependent Cushing's syndrome followed in two clinics in Canada, six cases with intestinal perforation were identified over 15 years. Age of patients ranged from 52 to 72, five females and one male, four with Cushing's disease and two with ectopic ACTH production, one from a pancreatic neuroendocrine tumor and one from medullary carcinoma of the thyroid. Five had diverticular perforation and one had intestinal perforation from a stercoral ulcer. All cases had their lower intestinal perforation when the cortisol production was high, and one patient had diverticular perforation 15 months prior to the diagnosis of Cushing's disease. As in previously reported cases, most had hypokalemia and abdominal pain with minimal or no peritoneal symptoms and this occurred during the active phase of Cushing's syndrome. Whereas all previously reported cases occurred in patients with 24-hour urinary free cortisol levels greater than 10-fold the upper limit of normal when measured and 11 of 14 patients had ectopic ACTH production, only one of our patients had this degree of hypercortisolism and four of our six patients had Cushing's disease. Similar to exogenous steroid use, patients with endogenous hypercortisolism also have a higher risk of intestinal, in particular diverticular, perforation and should be monitored closely for its occurrence with a low threshold for investigation and surgical intervention. Elective colonoscopy probably should be deferred until Cushing's syndrome is under control.